2015
DOI: 10.1038/srep11468
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-modified Substrate for Modulating Gland Tissue Growth and Morphology In Vitro

Abstract: In vitro fabricated biological tissue would be a valuable tool to screen newly synthesized drugs or understand the tissue development process. Several studies have attempted to fabricate biological tissue in vitro. However, controlling the growth and morphology of the fabricated tissue remains a challenge. Therefore, new techniques are required to modulate tissue growth. RGD (arginine-glycine-aspartic acid), which is an integrin-binding domain of fibronectin, has been found to enhance cell adhesion and surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…3A-C). Consistent with previous results, neutralization of FGF7 and FGF10 with their specific antibodies significantly suppressed SMG growth (Taketa et al, 2015), which was, however, partially restored by further MCSF supplementation (Fig. 3D,E).…”
Section: Mcsf Regulates Fgf7 and Fgf10 Expression Via Pi3k Signalingsupporting
confidence: 81%
“…3A-C). Consistent with previous results, neutralization of FGF7 and FGF10 with their specific antibodies significantly suppressed SMG growth (Taketa et al, 2015), which was, however, partially restored by further MCSF supplementation (Fig. 3D,E).…”
Section: Mcsf Regulates Fgf7 and Fgf10 Expression Via Pi3k Signalingsupporting
confidence: 81%
“…Therefore, our findings would be helpful in developing a biophysical model to analyze the dynamics of multicellular interactions in 3D cell aggregates. 20 This result was noteworthy because RGD enhanced SMG growth along with both, bud formation and duct elongation. 34 Previous reports regarding salivary branching identified FN as a key regulator of cleft formation.…”
Section: Discussionmentioning
confidence: 89%
“…20 Therefore, we used it as a negative control to confirm the sole effect of exogenous FN supplementation. Previously, we showed that stiff alginate hydrogel sheet substrates (184 kPa) can attenuate SMG growth.…”
Section: Fn Induces Branching Of Epithelium and Marked Ductal Elongmentioning
confidence: 99%
See 2 more Smart Citations